The electronic structure of SrCu2O2 studied by synchrotron radiation excited photoemission and hybrid exchange density functional calculations - Hu, J; Payne, D; Egdell, R; Harrison, N; Dhanak, V (2007)
Photoemission spectra of K-doped SrCu2O2 excited with vacuum ultraviolet synchrotron radiation have been measured over a range of photon energies between 36 eV and 164 eV. Intensity changes in the spectra with changing photon energy show that the states at the top of the valence band are of dominant Cu 3d atomic character, although there is evidence for significant hybridisation between O 2p and Cu 3d states. The experimental results are compared with partial densities of states derived from calculations using a hybrid exchange approximation to density functional theory. © 2007 Elsevier B.V. All rights reserved.